Menumbuhkan minat baca anak MI/SD dengan media buku bergambar seri - Lilis Sumaryanti (Universitas Muhammadiyah Ponorogo, 2020)
Interest in reading Indonesian people, especially the level of MI/SD children is still relatively low because they prefer playing online games, watching television etc. This factor causes their ability to read is still lacking. In addition, there are reading books (both storybooks and textbooks) in school institutions that are still monotonous with colourless pictures so that children are easily bored and are not interested in reading them. Based on the above phenomenon, the reading interest of MI/SD children must be increased by the teacher because